Overview of The Level of Knowledge About Preparedness to Face Flood Disasters in Joyontakan District, Kratonan Surakarta Public Health Center (Puskesmas) Working Area - Noorratri, Erika Dewi; Sari, Irma Mustika; Shing, Lin Chun (Adi Husada Nursing Journal, 2024)
A disaster is an occurrence that cannot be predicted when it will occur and can cause injuries or lives, as well as result in damage and loss. Preparedness efforts in facing disasters must be increased to reduce the risk and impact of disasters. One of the factors in disaster preparedness is the level of knowledge. Knowledge is one of the main factors and is the key to preparedness for facing disasters. The knowledge a person has can usually influence attitudes and concern for preparedness in anticipating a disaster. Method: quantitative with descriptive research methods, the total sample was 53 people, in May 2024 in RT.02 RW.01 Joyontakan Village, Surakarta City. The sampling technique used total sampling. Results: An overview of the level of community knowledge in RT.02 RW 01, Joyontakan Subdistrict, Surakarta City showed that the majority of the good knowledge level was 57%. Discussion: The community will have good knowledge that can be obtained from the experience of experiencing flood disasters in their area. This experience can provide additional knowledge for residents of areas that are prone to flood disasters. The flood disaster that has been experienced by residents has influenced the community's attitude and concern to be ready and ready to anticipate when a flood disaster occurs.